MRI-based radiosurgical planning: implications in imaging timing - Stross, William C.; Malouff, Timothy D.; Trifiletti, Daniel M.; Vallow, Laura A. (Annals of Translational Medicine, 2019)
Stereotactic radiosurgery (SRS) is now an accepted standard of care for patients with brain metastases. Many different platforms and workflows exist for delivering SRS, leading to variations in treatment delivery, such as elapsed time between stereotactic planning magnetic resonance imaging (MRI) and date of first radiosurgery. Salkeld et al. attempts to standardize the timing between planning MRI and repeat MRI before radiosurgery to evaluate for differences in target delineation (1). There were remarkable changes over a relatively short period of time, and the authors recommend a short interval between planning MRI and treatment, allowing for more accurate radiosurgical intervention.